2018
DOI: 10.1093/aobpla/ply045
|View full text |Cite
|
Sign up to set email alerts
|

The relative weight of ontogeny, topology and climate in the architectural development of three North American conifers

Abstract: Knowledge of plant architecture allows retrospective study of plant development, hence provides powerful tools, through modelling and simulation, to link this development with environmental constraints, and then predict its response to global change. The present study aims to determine some of the main endogenous and exogenous variables driving the architectural development of three North American conifers. We measured architectural traits retrospectively on the trunk, branches and twigs of whole tree crowns f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 63 publications
0
6
0
Order By: Relevance
“…[38] has found null and strong effect of shade on the production of long shoot in Betula pubescens depending on the year, suggesting that Atlas cedar is less sensitive to shading because the short shoot production of neither the branch order 2 nor the branch order 3 was affected by shading. Suzuki and Maki Suzuki [27] reported that, in Eurya japonica, the annual shoot length decreased with increasing branching order as has been found for many young and adult conifers [11,12,14] like pines and spruce [13].…”
Section: Discussionmentioning
confidence: 65%
See 2 more Smart Citations
“…[38] has found null and strong effect of shade on the production of long shoot in Betula pubescens depending on the year, suggesting that Atlas cedar is less sensitive to shading because the short shoot production of neither the branch order 2 nor the branch order 3 was affected by shading. Suzuki and Maki Suzuki [27] reported that, in Eurya japonica, the annual shoot length decreased with increasing branching order as has been found for many young and adult conifers [11,12,14] like pines and spruce [13].…”
Section: Discussionmentioning
confidence: 65%
“…Colombo and Templeton [13] have revealed that the annual shoot length was strongly correlated with branch position in the crown, thus with branch age in pines and spruce. In the same way to the latter authors, Buissart et al [14] demonstrated that the annual shoot length and the total number of branches and whorled branches were highly variable and decreased with age and with increasing branching order for Picea mariana, Pinus banksiana, and Pinus strobus. In contrast, Remphrey and Davidson [15] announced that generally, older branches tend to grow slowly whereas lengths of current shoots of major order 1 branches were found to decrease with increasing depth in the crown [16].…”
Section: Introductionmentioning
confidence: 53%
See 1 more Smart Citation
“…The minimum number of individuals per species was 15, taking into account the number of plants commonly used in primary growth dynamics research (e.g. Poorter et al 2006;Stecconi et al 2017;Buissart et al 2018).…”
Section: Methodsmentioning
confidence: 99%
“…It may be hypothesized that primary-growth patterns could change, in evolutionary time, from continuous to rhythmic or vice-versa. This hypothesis may be tested by means of the evaluation of endogenous and environmental influences on the primary growth of woody plants (Buissart et al 2018). Such information is highly interesting, considering that current global tendencies point to increments in climatic variability for temperate regions (Matthews et al 2016), which would impact on plant fitness in future scenarios.…”
Section: Introductionmentioning
confidence: 99%